Ingestão e estado nutricional de selênio de fenilcetonúricos de 4 a 10 anos de idade em tratamento no serviço especial de genética do Hospital das Clínicas da UFMG - Michelle Rosa Andrade Alves (2009)
The aim of the study was to evaluate nutritional condition and alimentary intake of selenium in 54 patients prospectively presenting Phenylketonuria (PKU). Patients are between 4 and 10 years and they have been early diagnosed, treated and no related diseases were found. The study has been carried out in two phases, before and after utilizing a mixture of amino acids supplemented with selenium. Data collection for the second phase was carried out at least 90 days after the mixture introduction. Selenium nutritional status was evaluated through the analysis of alimentary and biochemical parameters. During the first phase, a form (QFFQ) quantitative foodfrequency questionnaire was used in order to evaluate selenium intake adapted for people on target. In relation to the biochemical parameters, selenium serum and free thyroxin (T4L) dosing was carried out, as well as eritrocitary Glutathione peroxidase (GPX) dosing in both phases of the study. The average age of the PKU children participating in the study was, 7,0 ± 1,8 years, 32% female gender. The average period of selenium supplementation was about 122,2 ± 25,1 days. From the total 72,9% of the daily mineral administration was made up by the amino acid composed supplemented with the mineral content during the time it was used. Results showed asignificant increase in the selenium serum concentrations (p<0,05), as well as GPX concentrations on erythrocyte after the mineral supplementation. In addition, a remarkable co-relation (p<0,05) between these two parameters was noticed. Selenium average ingestion increased significantly (p<0,001) reaching DRI recommendation. Free T4 serum concentrations were normal, despite the serum concentration of free T4 were above the maximum reference limit in nine of the patients. After supplementation none of them presented alterations on hormonaldosing. The average concentration of this hormone showed normal on both phases, but significant reduction of those concentration (p<0,001) were noticed after supplementation with selenium. Results showed statistically a significant co-relation between the average selenium serum concentrations and eritrocitary GPX, as well as between that dosage and concentrations of free T4 before supplementation with selenium and amino acids. Results on this study showed supplementation withselenium by means of proteinic substitute effective, therefore, making it reasonable for supplementation and continuous maintenance of selenium ingestion recommendable for treating PKU.